Formation of sedimentary bedding couplets in the Western Interior Seaway of North America - Implications from Climate System Modelling - Flögel, Sascha; Hay, William W.; DeConto, R. M.; Balukhovsky, A. N. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
We use global climate simulations across one precessional cycle to investigate the effect of orbitally induced climatic changes on sedimentation in the Western Interior Seaway (WIS) of North America at the Cenomanian/Turonian boundary. The simulations include a control run with no orbital eccentricity and hence no precession cycle, and four runs with varying precession with an eccentricity of 0.05 having (1) northern spring equinox at perihelion, (2) northern winter solstice at perihelion, (3) northern fall equinox at perihelion, and (4) northern summer solstice at perihelion. These numeric climate simulations and field observations suggest that the WIS at the Cenomanian/Turonian boundary can be divided into three latitudinal units: (1) A northern unit (Alberta–Montana) between 51°N and 71°N paleolatitude where conditions remained constant under the influence of steady inflow of low salinity, cool waters which were devoid of calcareous plankton flowed in from the Arctic, preventing the development of bedding couplets. (2) A central unit (Wyoming–Colorado) between 41°N and 51°N paleolatitude where runoff from Western North America (WNA) was reduced by more than half when the northern hemisphere winter solstice coincided with perihelion, where bedding couplets are well developed. The central part of the WIS was characterized by warm saline waters with abundant calcareous plankton. However it experienced high summer surface runoff from the Sevier Highlands to the west during all orbital configurations except when the winters were unusually warm, with the northern hemisphere winter solstice occurring at perihelion. Seasonal dilution of the surface waters of the seaway may have resulted in formation of a “fresh water lid” with stratification of the water column throughout most of the precession cycle. When the northern hemisphere winter solstice was at perihelion, reduced runoff would promote vertical mixing. Concomitantly, a steady detrital sediment supply would occur in summer throughout the precession cycle except ...